Planejamento e aplicação de recursos do Programa Dinheiro Direto na Escola em uma instituição municipal de tempo integral em Telêmaco Borba - Chudrik, André (2013)
This research investigates the planning and implementation process of the program resources Money Direct to School (PDDE), in a full-time municipal school in Telêmaco Borba city. The descriptive nature of the research is bases on literature review and on educational manager’s interview. The research is guided by the following research problem: how does the planning process of Program resources Money Direct to School (PDDE) work in municipal institution from Telêmaco Borba, Paraná state, according to educational manager view? The main objective is to understand the planning and implementation process of PDDE resources in elementary school from Telêmaco Borba. Such understanding can foster strategic actions and help ensure quality, free and public education, as prescribed by law. For that, it is described the planning and implementation of PDDE resources and, based on the principles of public administrations, some actions of that program are analyzed. The paper is organized into three parts. In the theoretical framework, policies, planning and management of public resources and PDDE are provided. After that, the methodological procedures are defined and, finally, the data analysis and conclusion are presented. The analysis suggest that the planning follow the program guidelines, but that the resources implementation is not enough and does not meet the real needs of the studied school to promote improvement in students’ performance. The principles of public administration are present in the PDDE actions, especially the efficiency principle as the one that requires further improvement, by both governments and educational manager.